2020
DOI: 10.1111/add.15252
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between socio‐economic status and lottery gambling across lottery types: neighborhood‐level evidence from a large city

Abstract: Background and aims Lottery gambling participation tends to be higher among lower socio‐economic status (SES) individuals, but it is unclear how this relationship differs as a function of lottery type. We estimated how the relationship between SES and lottery gambling rates varies across different types of lottery gambling: fixed‐prize, progressive‐prize (jackpot) and instant‐win (scratch card) lottery tickets in a large Canadian city. Design Neighborhood‐level lottery purchase data obtained from the Ontario L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…We attempted to address this problem by excluding FSAs with low populations (less than 1000 residents): this mainly targeted commercial FSAs in the downtown area of Toronto, which have inflated lottery purchase rates presumably due to commuter activity. In a recent examination of this same dataset, we found that fixedprize lotteries are purchased more by individuals in lower-socioeconomic status (SES) than in higher-SES neighborhoods (Fu et al, 2021), suggesting that the observed purchase rates of individual FSAs likely reflects the behaviour of their residents. At the same time, SES has previously been linked to problem gambling (Orford et al, 2010;Welte et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…We attempted to address this problem by excluding FSAs with low populations (less than 1000 residents): this mainly targeted commercial FSAs in the downtown area of Toronto, which have inflated lottery purchase rates presumably due to commuter activity. In a recent examination of this same dataset, we found that fixedprize lotteries are purchased more by individuals in lower-socioeconomic status (SES) than in higher-SES neighborhoods (Fu et al, 2021), suggesting that the observed purchase rates of individual FSAs likely reflects the behaviour of their residents. At the same time, SES has previously been linked to problem gambling (Orford et al, 2010;Welte et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Our results found that those with higher incomes were more likely to participate in the M$V lottery which is opposite to expectations. Those on lower incomes are more likely to participate in lotteries generally 13 14 . Our result maybe because of the specific context of COVID-19 where a large proportion of the population was or had been in a severe lockdown, and so the lottery was also perceived as a reward for their patience and for already being vaccinated and that this perception was more widely held by those with higher incomes.…”
Section: Discussionmentioning
confidence: 99%
“…Though the literature on lotteries suggests those on lower incomes are more likely to enter, recall that vaccination competitions are not lotteries as they do not involve gambling. 14 15 . The financial incentives offered through entry into M$V were likely to have been perceived as a reward for getting vaccinated and that this perception may have been more widely held by those with higher incomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower income individuals spend a greater proportion of their income on lottery gambling than those with higher income [2,4,10,11]. Furthermore, ticket sales not only correlated with levels of income, but also with lower socioeconomic status (SES) [8,5]. As such, it is important to visualize and explore this data for analysis by experts or regular users who wish to discover trends.…”
Section: Statement Of Needmentioning
confidence: 99%